Evaluasi Program Pengukuran Tinggi dan Berat Badan Siswa di TK Yayasan Harapan Sejati Menggunakan Model CIPP - Sigalingging, Jelita R; Dharma, Irtiyah Nazwa; Muslihani, Khaira; Salsabila, Nazwa; Lumbanraja, Sri Rezeki; Manalu, Yolanda Br (Veritas: Jurnal Penalaran dan Riset Mahasiswa Pendidikan, 2025)
This study aimed to evaluate the implementation of the height and weight measurement program for students at TK Yayasan Harapan Sejati using the CIPP model (Context, Input, Process, Product). A descriptive quantitative approach was employed, with the principal and classroom teachers as research subjects, as they were directly involved in the program. Data were collected through structured observation sheets and a four-point Likert scale questionnaire, then analyzed descriptively to assess the effectiveness of each CIPP component. The results indicate that the program is effective: the context aligns with the actual needs for monitoring child growth, inputs such as measuring tools and teacher competence are sufficient, the process is conducted orderly and safely, and the program outputs provide accurate data useful for monitoring children’s health. In conclusion, the height and weight measurement program at TK Yayasan Harapan Sejati effectively supports the growth monitoring of early childhood students.